Studi Terhadap Kosakata Bahasa Arab Dalam Bahasa Minangkabau - Hanif, Akhyar (ARABIYATUNA : Jurnal Bahasa Arab, 2017)
This paper seeks to reveal the influence of Arabic on Minangkabau language, and trying to find relationships between these languages. Constitute Arabic as the language of the Quran as the language of scripture, then expand and spread almost to all regions and countries in this world as the development of Islam to various regions including Minangkabau. History also proves that Arabic has a very big influence in the development of vocabulary in Minangkabau language. Therefore, this paper tries to trace the Arabic vocabulary that goes into Minangkabau. This study proves that there are more than 500 Minangkabau vocabulary which is the absorption of Arabic, and of course this study will be much longer if examined further from every area in Minangkabau